Bibliometric analysis on street network components in influencing genome of urban morphologies - Mohd Nor, Marina; Hj. Mohd. Noor, Norzailawati; Asmawi, M. Zainora (IIUM Press, 2021)
Bibliometric or thematic analysis is a type of research approach used in the library and information science. This paper aims to analyze the street network elements as one of the city organisms that is integral to the city's cohesive form. The street network also influences the genome of urban morphology. In this research, the qualitative analysis and statistics were used to describe a publication pattern in the given body of literature. The publications from Scopus and Web of Science were compiled and analyzed in depth. The finding showed that urban morphologies' genome had been indeed influenced by the street network components, namely street hierarchy, permeability and legibility, streetscapes and pedestrian movement. The components were mutually present in the urban morphology genome, which can accelerate the movement within the city. The street hierarchy shows that this structure becomes an organism that viral for the city's development. The transition of the street's hierarchical system contributes to the changes or evolution of the city from time to time. Meanwhile, permeability represents the image of the city. The physical and visual images of a city are essential to leapfrog the city to reach the global recognition level. However, the inconsistency of implementation of the permeability element will negatively impact the place. Urban streetscape is essential to avoid a negative impression on the city image, which should have otherwise provided a city's visual richness. Lastly, pedestrian accessibility through appreciation of the street network attracts the movement within the public spaces. In conclusion, the street network components were found to have influenced onto the city's morphology over time and became a backbone for the latter, reflecting the urbanization process. Nevertheless, based on the bibliometric analysis, the study of street network morphology has not been sufficiently extended from many Asian countries' theoretical ground.